STIMULASI PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN MELALUI ALAT PERMAINAN BOLA PENGUMPUL BINTANG (BOLUMTANG) - Andiya, Aflah; Sartika, Lea; Sain, Satifa; Widjayatri, Rr. Deni (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2023)
Social emotional development plays an important role for the mental stability of children in the future so that it requires stimulation in accordance with developmental needs and adequate educational game tools. The star collecting ball game (BOLUMTANG) is here as an educational game tool that educators can use in developing social emotional aspects for children. The purpose of the study was to stimulate the social emotional development of children aged 5-6 years using the star collecting ball game media (BOLUMTANG). This research uses descriptive qualitative methods, documentation, research instruments with observation and practice data analysis techniques through the star collection ball educational game tool (BOLUMTANG). The study subjects were applied to 2 children with initials J and D kelompok B in UPI Labschool Kindergarten, Serang City, Banten Province. The results showed that the indicators of childrens social emotional development were obtained by childrens enthusiasm in playing star collecting ball game, children playing with friends without discriminating, being patient in waiting for their turn to throw the ball, obeying the rules of the game, being able to show self-confidence. Showed Expressions before and after the game, and tidied up the toys after use. All the social emotional indicators of children J and D in the study were well developed. Furthermore, it is hoped that this research can be used by educators in stimulating child development, especially developing early childhood social emotional.